Nivel de cultura de ahorro en el vendedor del mercado Teniente Manuel Clavero Muga - Punchana 2020 - Ramirez Reátegui, Daniel Elias (2022)
The general objective of this research work was to determine the level of savings culture in the market merchant Teniente Manuel Clavero Muga of the Punchana district. The research, due to its approach, was quantitative, prospective strategy, simple descriptive level and non-experimental research design. The study population is made up of eighty-two (82) merchants of the different product sales categories, who are dedicated to daily sales and are registered in the official register of market merchants. The sample consisted of Forty-eight (48) merchants, who were present at the time of the application of the data collection instrument, inclusion and exclusion criteria were taken into account, the technique used was the survey and the The instrument applied was the questionnaire, which consisted of twenty questions. The data obtained through the data collection instrument was analyzed taking into account the objectives and the research hypothesis and later expressed in a Basic Data Matrix (MBD). The information was analyzed, processed and tabulated through the statistical package Startical Product and Service Solutions (SPSS) version 25. The results expressed that 17.4% of merchants had a very low saving level, 17.4% a low level, 45.7% a medium level and 19.6% a high level, therefore has a medium level of savings culture.